2016
DOI: 10.1182/blood.v128.22.1913.1913
|View full text |Cite
|
Sign up to set email alerts
|

CML Treatment in Dutch Hospitals with Low Patient Volumes Is Associated with a Substandard Quality of Molecular Response Monitoring

Abstract: Introduction Chronic myeloid leukemia (CML) is a relatively rare condition with approximately 170 new patients per year in the Netherlands. Patients at risk of progression to advanced stage disease need to be identified based on their molecular BCR-ABL1response, for which detailed guidelines are available. We evaluated the quality of molecular monitoring in Dutch clinical practice. Methods Chronic phase CML patients with a minimum of one year available follow-up wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…This might be a reason why the observed number of cytogenetic analyses is lower than recommended. These results are in accordance with the work of Geelen et al 15 Some years ago, we had reported differences in survival between teaching hospitals, municipal hospitals, and office-based physicians. 35 Here we found differences with regard to cytogenetic but not with regard to molecular evaluations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This might be a reason why the observed number of cytogenetic analyses is lower than recommended. These results are in accordance with the work of Geelen et al 15 Some years ago, we had reported differences in survival between teaching hospitals, municipal hospitals, and office-based physicians. 35 Here we found differences with regard to cytogenetic but not with regard to molecular evaluations.…”
Section: Discussionsupporting
confidence: 93%
“…A regular cytogenetic and/or molecular monitoring has been considered necessary for a successful treatment and a prolonged survival. [13][14][15] However, it has been shown that at least in the United States, the number of molecular examinations is far away from the guidelines' recommendations. 16 Thus, the aim of our study was to evaluate whether the prescribing of TKIs and the subsequent monitoring of patients with CML in Germany follow the current European LeukemiaNet (ELN) recommendations and whether prescribing is sufficient to allow for a satisfactory patients' compliance.…”
mentioning
confidence: 99%
“…Preliminary results from a national populationbased study showed inadequate monitoring in the first year of TKI treatment in 28% of the newly diagnosed CML-CP patients in the Netherlands, whereas patients who received optimal molecular monitoring had a significant higher overall survival [9]. This is consistent with other studies, showing that 54% of the patients were monitored less than 3 times a year and had a significantly higher risk of progression to advanced phase disease and death [10].…”
Section: Introductionsupporting
confidence: 81%
“…When these response criteria are not met and patient adherence is optimal, the TKI received as current treatment should be substituted with an alternative TKI. In the Netherlands, a rate of patients receiving adequate molecular monitoring of 72% was observed [9].…”
Section: Probabilities: Physician Adherencementioning
confidence: 99%
See 1 more Smart Citation